The people of the city - Khalil, Omnia (AUC Knowledge Fountain, 2014)
In this thesis I argue that people in Ramlet Bulaq constitute their relationship to space in terms of laboring, and in the process produce the very space named Ramlet Bulaq. My inquiry is about the relationship between labor and space, particularly how people constitute themselves in place by what they are doing, i.e. laboring. Ramlet Bulaq as a space and the transformations that happened occasioned shifts in people's practices of laboring. Moreover, laboring comprises the pretext of their strategies and tools in coping, adapting, and fighting back. In short, I conceptualize laboring at the heart of political and social relations of power that produce the space of Ramlet Bulaq and shape the making of the people of Ramlet Bulaq. In this thesis I aim to unpack the relationship between people and their space in terms of their laboring which is reflected in the histories of the making of Ramlet Bulaq as shaped by interactions, confrontations and encounters with circuits of power, which range from the municipalities, the police station, the Nile City towers administration, the local mosque, the local popular committee, the men in the neighborhood, the non-governmental organizations and the activists. My conceptual and methodological frameworks emphasize this understanding on the How of Ramlet Bulaq, not only What is Ramlet Bulaq (Deleuze 1987: 2983). I am using the how here referring to the different relations between violence, labor, space, state and capital in addition to the potentialities. Laboring represent the potentialities in the everyday doings of the residents in the space; parallel to the Nile City Towers, which represent capital interests investing in their space and business, and the apparatus of the state which allied with the Nile Towers by supporting their plans and investments in the name of development and progress. To just name one instance of this mutual alliance between state and capital: an agreement published in the Official newspaper Al Wakae Al Masreya (The Egyptian Gazette) on June 20th, 2012 declared that the government would legally take over the land of Ramlet Bulaq. Subsequently, The Nile City Tower representatives started buying land plots from the residents of Ramlet Bulaq. Those developmental plans are for the benefit of the urban elite population and managed by the capital and the state (Bhaduri 2007). As Harvey asserts commercialism and property development occupy the space of a public-private partnership for the benefit of private rather than civic gain by the money of the public (Harvey 1990: 422).